2017
DOI: 10.2220/biomedres.38.221
|View full text |Cite
|
Sign up to set email alerts
|

<b>DEC1 promotes hypoxia-induced epithelial-mesenchymal transition (EMT) in human hepatocellular carcinoma </b><b>cells </b>

Abstract: Differentiated embryonic chondrocyte (DEC) 1 has been reported to be involved in cell differentiation, hypoxia response, and cancer progression. Recent studies have demonstrated that hypoxiainducible factor (HIF)-1α induces epithelial-mesenchymal transition (EMT) in carcinoma cells to facilitate cell invasiveness and metastasis. However, it remains unclear whether DEC1 participates in hypoxia-mediated EMT processes. In the present study, we reported that hypoxia induced DEC1 expression in hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…This method can be extended to the interaction of other associated genes. Previous studies indicated that EMT markers are associated with human tumor metastasis ( 44 46 ). In the present study, only the association between miR-153 and SNAI1 in LSCC cells was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be extended to the interaction of other associated genes. Previous studies indicated that EMT markers are associated with human tumor metastasis ( 44 46 ). In the present study, only the association between miR-153 and SNAI1 in LSCC cells was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, overexpression of BHLHE40 antagonized apoptosis induced by 8-MOP by abolishing the decrease of survivin and the activation of caspase-3 [134]. Hypoxia-induced BHLHE40 promoted EMT and induced metastasis in HepG2 cells [135,136]. Subsequent II receptor (R2), which recruits and phosphorylates a type I receptor (R1).…”
Section: Bhlhe40 As a Mediator Of Hypoxia-regulated Tumor Progressionmentioning
confidence: 99%
“…Differentiated embryonic chondrocyte-expressed gene 1 (DEC1), also called STRA13 in mouse and SHARP2 in rat, is a bHLH transcription factor that is involved in the regulation of cell growth and differentiation (Qian et al 2012 ; Rossner et al 1997 ). It has been reported that DEC1 played an important role in the regulation of the EMT in hepatocellular carcinoma (Murakami et al 2017 ). Loss of DEC1 expression is an early event in the development of lung cancer (Giatromanolaki et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%